A Flow Pattern Study Of Temenggor Dam Hydraulic Physical Model - Khan, Muhammad Nasri Nasehir (Universiti Sains Malaysia, 2022)
Recently, the sustainability of hydroelectric dams has been questioned due to their reliability and efficiency. Factors such as sedimentation, erosion and vortex formation at the dams have adversely impacted the sustainability of the dam to function optimally. A stable and uniform flow pattern at the dam’s upstream is important to ensure the sustainability of dam is preserved due to minimal impacts of erosion, sedimentation and vortex. The study had assessed the potential of sedimentation, erosion and vortex formation at Temenggor Dam, based on the flow pattern formed via hydraulic physical model with a scale of 1:100. There are four cases have been tested which are Case 1 (the position of water inlet at the middle and at stage of 0.38m), Case 2 (the position of water inlet at the middle and at stage 0.34m), Case 3 (the position of water inlet at the side and at stage of 0.38m) and Case 4 (the position of water inlet at side and at stage 0.34m). Based on Case 3, the range of flow velocities obtained was 0.3 – 2.1 m/s at 20% from water surface, leading to erosion which occurred alongside the bank of the dam and sedimentation which focussed on the side of the dam that threatened the stability of the dam due to the concentrated load of sediment. Vortex type 5 – 6 had been identified for a period of 15-30s which requires immediate preventive measures to ensure sustainability of the Temenggor Dam. The study found that flow pattern at the upstream of the Temenggor Dam was influenced by the position of water inlet from dam’s upstream, flowrate of the dam and the depth from the water level.